The Influence of Reward and Punishment Systems on Student Discipline - Aylin Erdogan; Cemil Kaya; Azamat Nazarov (International Journal of Educational Narratives, 2025)
Background. The role of reward and punishment systems in shaping student discipline has long been a subject of interest in educational psychology. Schools often rely on these systems to promote desirable behaviors and deter misconduct, yet the effectiveness of these strategies remains debated. Purpose. This study explores the influence of reward and punishment systems on student discipline in secondary schools, focusing on how these strategies affect student behavior and academic performance. Method. The research uses a mixed-methods approach, combining quantitative surveys to assess student perceptions and qualitative interviews with teachers and school administrators. Results. The results reveal that both reward and punishment systems have a significant impact on student discipline, but the nature of the influence depends on the consistency, clarity, and fairness of their implementation. Reward systems were found to be more effective in fostering positive behaviors and improving academic performance, while punishment systems were more effective in deterring misconduct when applied consistently. However, excessive reliance on punishment led to negative emotional outcomes for students. Conclusion. The study concludes that a balanced approach, where rewards are used to encourage positive behaviors and punishments are applied sparingly and fairly, is the most effective strategy for promoting student discipline.